Overexpression of Global Regulator PbrlaeA Leads to the Discovery of New Polyketide in Fungus Penicillium Brocae HDN-12-143 - Wang, Lu; Zhang, Xianyan; Zhang, Kaijin; Zhang, Xiaomin; Zhu, Tianjiao; Che, Qian; Zhang, Guojian; Li, Dehai (Frontiers in Chemistry, 2020)
Overexpression of the PbrlaeA gene of the fungus Penicillium brocae HDN-12-143 resulted in the isolation of four compounds including fumigatin chlorohydrin (1), whose configuration has not been reported before, and one new compound iso-fumigatin chlorohydrin (2). All structures including absolute configurations were elucidated on the basis of comprehensive spectroscopic data, 13C NMR calculations, and ECD calculations. Compounds 1 and 2 exhibited cytotoxic activity against HL-60 with IC50 of 20.86 and 24.02 μM.